Emergency interventions for patients with suspected acute myocardial infarction (Research, Society and Development, 2020)
Acute Myocardial Infarction (AMI) represents an important public health problem in Brazil and worldwide, with high rates of incidence and mortality. The objective was to conduct a bibliographic survey about emergency interventions for patients with suspected acute myocardial infarction. It is an integrative literature review, the search was carried out in the databases: LILACS, SCIELO and BDENF, via VHL. The articles were collected between May and June 2020. The descriptors: Emergency, Patient assistance and Acute myocardial infarction were used. After applying the inclusion criteria, 10 studies remained. Individuals who have an acute myocardial infarction need intervention as soon as possible, and the initial care provided relates to emergency procedures, in order to prevent the condition from evolving to a more serious state, or even to death. It was concluded that emergency interventions provided to patients with suspected infarction are essential for the patient's prognosis, and that the correct assessment, rapid diagnosis and the beginning of appropriate treatment prevent injuries resulting from this clinical condition.